Integrated aquaculture in arid environments - Stephen Goddard; Fatma Saif Al-Abri (Journal of Agricultural and Marine Sciences, 2019)
Around one third of the globe is classified as desert or arid (<200mm rain annually) and most such regions lack food security. Traditional freshwater aquaculture is often a marginal activity and competes with agriculture for limited water resources. Developing technologies offer new opportunities to increase productivity of aquaculture through integration with vegetable production in aquaponic systems and to reduce water requirements through the application of biofloc technology. Aquaponic systems combine aquaculture and hydroponic plant production and are integrated within a re-cycled water system. Fish waste metabolites provide the nutrients for plants grown in soil-less, hydroponic systems. Biofloc farming systems operate with minimum or zero water exchange. Suspended biofloc particles develop in fish tanks under conditions of full aeration and controlled carbon to nitrogen ratios. They comprise algae, bacteria, protozoa and particulate organic matter held in a loose matrix. They provide in-situ treatment of harmful fish metabolites, are protein rich, contain essential fatty acids, vitamins and minerals and supplement the diets of filter-feeding farmed species. The integration of fish culture with vegetable production provides new opportunities for small and medium enterprises. Integrated farms occupy a small footprint, optimise the use of resources and can be built close to population centres. This paper reviews current developments in aquaponics and biofloc technology against the background of food security needs in arid regions.